Implementation of The Cooperative Integrated Reading and Composition (Circ) Method in Learning Narrative Writing for Elementary Students - 'Adilah Hayya, Luma’ul; Wachid Bambang Suharto, Abdul (International Proceedings of Nusantara Raya, 2023)
This qualitative research aims to analyze the application of the methodCooperative Integrated Reading and Composition (CIRC) in learning to write narrative essays for elementary school students. This study uses a descriptive qualitative approach. The research subjects were 10 grade 4 elementary school students consisting of 5 boys and 5 girls. Data was collected through observation, interviews and documentation. The results of the study show that in using the CIRC method in writing narratives, there are several important steps that must be taken, such as reading, discussing, determining focus, making summaries, writing narratives, revising and editing, and presenting. However, there are several obstacles that may be encountered, such as students' difficulties in reading, writing, and communicating, lack of student participation which can slow down the learning process, and the lack of teacher experience in using this method. Therefore, several solutions are needed to overcome these obstacles, such as planning lessons carefully and choosing the right material, providing additional support to students who need it, providing motivation and appreciation to active students, and holding meetings with parents to explain the benefits of the CIRC method for student learning. . By taking these steps, it is hoped that the CIRC method can be effective in improving students' writing skills and collaboration in learning. as well as holding meetings with parents to explain the benefits of the CIRC method for student learning. By taking these steps, it is hoped that the CIRC method can be effective in improving students' writing skills and collaboration in learning. as well as holding meetings with parents to explain the benefits of the CIRC method for student learning. By taking these steps, it is hoped that the CIRC method can be effective in improving students' writing skills and collaboration in learning.